Estimating statistics of sky brightness using radio interferometric observations - Dutta P.; Nandakumar M. (My University, 2025)
Radio interferometers are used to construct high resolution images of the sky at radio frequencies and are the key instruments for accessing the statistical properties of the evolution of neutral hydrogen over cosmic time. Here we use simulated observations of the model sky to assess the efficacy of different estimators of the large-scale structure and power spectrum of the sky brightness distribution. We find that while the large-scale distribution can be reasonably estimated using the reconstructed image from interferometric data, estimates of the power spectrum of the intensity fluctuations calculated from the image are generally biased. This bias is found to be more pronounced for diffuse emission. The visibility based power spectrum estimator, however, gives an unbiased estimate of the true power spectrum. This work demonstrates that for an observation with diffuse emission the reconstructed image can be used to estimate the large-scale distribution of the intensity, while to estimate the power spectrum, visibility based methods should be preferred. With the upcoming experiments aimed at measuring the evolution of the power spectrum of the neutral hydrogen distribution, this is a very important result. © 2019 National Astronomical Observatories, CAS and IOP Publishing Ltd..